1988
DOI: 10.1093/infdis/157.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Vaccines in Patients with Chronic Renal Failure Before Dialysis

Abstract: Hepatitis B remains a significant risk to patients receiving chronic hemodialysis, but no certain method of prevention has been identified. We tested two vaccines, plasma-derived vaccine (40-micrograms dose) and recombinant-derived vaccine (40-micrograms and 20-micrograms doses), in 61 patients with chronic renal failure who were not yet dependent on dialysis. Patients were followed up clinically and with laboratory tests of kidney function and hepatitis B virus serology for one year. Significantly more recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
6

Year Published

1988
1988
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 20 publications
1
37
0
6
Order By: Relevance
“…2,8 Higher rates of protection can be achieved by vaccinating end-stage renal disease patients before they begin dialysis. 9 Despite the success of long-standing infection control practices for preventing HBV infections among chronic hemodialysis patients, HBV transmission in this setting remains problematic. Recently, five hepatitis B outbreaks in chronic hemodialysis units were reported during 1 year in the United States.…”
mentioning
confidence: 99%
“…2,8 Higher rates of protection can be achieved by vaccinating end-stage renal disease patients before they begin dialysis. 9 Despite the success of long-standing infection control practices for preventing HBV infections among chronic hemodialysis patients, HBV transmission in this setting remains problematic. Recently, five hepatitis B outbreaks in chronic hemodialysis units were reported during 1 year in the United States.…”
mentioning
confidence: 99%
“…Bu hastalarda T-lenfosit ve antijen sunan hücrelerde fonksiyon bozukluğu olduğu düşünülmektedir [13][14][15]. Bazı çalışmalarda diyalizsiz takip edilen KBH hastalarında daha yüksek antikor cevabının elde edilmesi, böbrek yetmezliğinin şiddeti ile immün cevabın korele olduğunu düşündürmektedir [13,16,17]. KBH hastalarında hepatit B aşılamasına yeterli cevap alınabilmesi için yüksek doz ve daha sık enjeksiyon yapılması önerilmiştir [10,18].…”
Section: Discussionunclassified
“…Recommendations include increasing the vaccine dose and/or the frequency of vaccination to maintain high levels of anti-HBs. Seaworth et al 66 reported that recombinant HBV vaccine given intramuscularly in the deltoid muscle in a three-dose schedule at 0, 1, and 6 months provided a seroconversion rate of 42%. After the dose was increased to 40 μg, the anti-HBs seroconversion rate increased to 69%.…”
Section: Discussionmentioning
confidence: 99%